Arabic Language Learning Management At SMP IT Ibnu Halim Medan - Karim, Zikrianul; Setiawan, Hasrian Rudi (Edumaniora : Jurnal Pendidikan dan Humaniora, 2023)
Learning Arabic is a process that is carried out between educators and students both in class and outside the classroom so that students are able to master Arabic. Management of learning Arabic is a means or wasilah so that the desired goals can be achieved. Management of learning Arabic includes planning, implementing, organizing, assessing and evaluating. Everything is designed to be effective and efficient. The participation of an educator is needed in improving the quality of language. Efforts made by educators in improving language development, can be through active and creative learning. An educator is required to understand the development of learning Arabic. After analyzing there are several supporting and inhibiting factors in learning Arabic. In this study the method used is descriptive qualitative and type of field research.